2008
DOI: 10.1371/journal.pone.0003102
|View full text |Cite
|
Sign up to set email alerts
|

Mcl-1 Is a Key Regulator of Apoptosis Resistance in Chlamydia trachomatis-Infected Cells

Abstract: Chlamydia are obligate intracellular bacteria that cause variety of human diseases. Host cells infected with Chlamydia are protected against many different apoptotic stimuli. The induction of apoptosis resistance is thought to be an important immune escape mechanism allowing Chlamydia to replicate inside the host cell. Infection with C. trachomatis activates the Raf/MEK/ERK pathway and the PI3K/AKT pathway. Here we show that inhibition of these two pathways by chemical inhibitors sensitized C. trachomatis infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
126
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(137 citation statements)
references
References 41 publications
7
126
0
4
Order By: Relevance
“…We found pronounced activation of MEK and ERK shortly after infection coincident with phosphorylation of Tarp and SHC1. Previous work suggested that rapid phosphorylation of ERK during chlamydial infection is linked to up-regulation of the anti-apoptotic protein MCL-1 (Rajalingam et al, 2008), which we found to be independent of SHC1 (unpublished data). Moreover, in our previous work, activation of both MEK and ERK was shown to be necessary for C. trachomatis at an advanced stage of infection; however, this activation was uncoupled from upstream signaling by RAS and RAF (Gurumurthy et al, 2010).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…We found pronounced activation of MEK and ERK shortly after infection coincident with phosphorylation of Tarp and SHC1. Previous work suggested that rapid phosphorylation of ERK during chlamydial infection is linked to up-regulation of the anti-apoptotic protein MCL-1 (Rajalingam et al, 2008), which we found to be independent of SHC1 (unpublished data). Moreover, in our previous work, activation of both MEK and ERK was shown to be necessary for C. trachomatis at an advanced stage of infection; however, this activation was uncoupled from upstream signaling by RAS and RAF (Gurumurthy et al, 2010).…”
Section: Discussionsupporting
confidence: 70%
“…In addition, Chlamydia subverts the function of the pro-apoptotic PKC by increasing diacylglycerol levels in the chlamydial inclusion membrane (Tse et al, 2005). Together, these observations suggest that Chlamydia prevents host cell apoptosis through a variety of mechanisms, likely acting sequentially as infection proceeds (Fan et al, 1998;Perfettini et al, 2002;Rajalingam et al, 2008). …”
Section: Any Bacterial Pathogens Translocate Effectormentioning
confidence: 89%
See 2 more Smart Citations
“…These differences will need to be reconciled in the future. In parallel, infection also leads to stabilization of IAP2 (inhibitor of apoptosis protein 2) and up-regulation of the prosurvival factor Mcl-1 (myeoloid cell leukemia) (Rajalingam et al 2006(Rajalingam et al , 2008Sharma et al 2011). Other mechanisms potentially include sequestration of Bad at the inclusion via 14-3-3b, and of protein kinase C-d (PKCd) through binding to diacylglycerol-enriched membranes in the vicinity of the inclusion (Scidmore and Hackstadt 2001;Tse et al 2005;Verbeke et al 2006). )…”
Section: Maintaining the Host Cell Alivementioning
confidence: 99%